Interactive video games to promote physical activity among healthy children and youths - Kowaluk, Aleksandra; Woźniewski, Marek (Pediatria Polska - Polish Journal of Paediatrics, 2019)
Physical activity is crucial in reducing the risk of civilisation diseases: type 2 diabetes, hypertension, obesity, osteoporosis, cancer, and depression. An adequate level of physical activity during childhood prevents the development of early atherosclerotic lesions, which result from obesity, hypertension, and dyslipidaemia, frequently appearing amongst children. Most children do not meet the basic physical activity guidelines. Children spend most of their time in a sitting position, which reduces their daily energy expenditure. Interactive video games (IVG) can be an alternative and attractive form of spending free time, which may contribute to reduction of children’s sedentary behaviour. The use of IVG in preventive health programs can become a way to increase the level of physical activity and reduce cardiometabolic risk factors. The aim of this study is to review the research on the impact of the IVG on the level of physical activity, sedentary behaviour, and energy expenditure of healthy children.